UPAYA PENANGANAN COVID-19 PADA MASA PPKM DARURAT DI DESA CIAPUS - Andani, Yuri Ayu; Kusumadinata, Ali Alamsyah (Universitas Djuanda, 2022)
With the increase in positive cases of Covid-19 every day, the government is preparing efforts to deal with COVID-19. One of the main focuses in handling COVID-19 is the implementation of Emergency PPKM (Implementation of Restrictions on Community Activities). These efforts are carried out in each region following central government regulations. This study aims to determine efforts to deal with Covid-19 by taking cases in Ciapus Village, Bogor Regency, West Java, Indonesia. This study uses a qualitative approach with a case study research method by taking an issue in the village of Ciapus. The study results show that the efforts made to tackle Covid-19 are by closing the trade area, which is in the red zone of Ciapus Village, the communication used is persuasive, and the community's response can work together by not crowding in the area.